Analisis Kemampuan Pemahaman Konsep Matematika pada Materi Segiempat Kelas VII - Lambok Simamora; Roida Eva Flora Siagian; Liza Cahyani (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
Research conducted at SMP Negeri 39 Bekasi aims to determine: The ability to understand mathematical concepts of students on quadrilateral material with an indicator of the ability to understand mathematical concepts used is killpatrick. The type of research used is descriptive qualitative. This research was conducted on 35 students, the method of taking the subject in this study was using purposive sampling, the subjects were taken as many as 9 students, namely 3 high-ability students, 3 medium-capable students, and 3 low-ability students. The data collection technique was carried out with test instruments that had been empirically validated and the results of interviews with the subject. The instrument used was in the form of 2 items on the ability of students to understand mathematical concepts on the rectangular material accompanied by interviews with students. The results of the study concluded that: The ability to understand mathematical concepts of class VII students of SMP Negeri 39 Bekasi for the 2019/2020 academic year was in the medium category.